Ethnic Segregation In Context: The Case Of Education In Vallecas - Puente De Vallecas - Poveda, David (Education Policy Analysis Archives, 2003)
This article presents an ethnographic analysis of the social conditions and ideological processes that help understand how students are distributed unequally between private and public schools on the basis of their ethnicity. To do so, it examines the form these mechanisms adopt in a particular area of Madrid (Spain): Vallecas-Puente de Vallecas. This part of the city has undergone dramatic social changes during the last fifty years and has a very intense social history in Madrid. Currently, it shows a high degree of ethnic segregation between schools depending on their status (public vs. ‘private-concerted’). Also, contrary to what is considered the usual tendency in Spain, even though this area is predominantly lower-middle class, the majority of students of these two districts are enrolled in private-concerted schools. These circumstances are explained through a folk theory present in the community regarding the role of private education in processes of social mobility and an emic categorization of the type of pupils who attend public and private-concerted schools. In the conclusions, two themes are discussed: (a) implications that this case has for practical implementations of policy measures geared at reducing the “dualization” of the Spanish educational system and; (b) some strands of research that could be followed in the study of the role the educational system plays in the construction of social inequality.